2011
DOI: 10.4067/s0717-95022011000200042
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Variations in the Formation of the Trunks of Brachial Plexus

Abstract: SUMMARY:Brachial plexus shows several variations in its formation and branching pattern. Variations in the formation of the trunks are very rare. We studied 44 dissected specimens specifically for variations in the formation of the trunks of the brachial plexus. 5 cadavers (11.3%) showed variations in the formation of the trunks. All the variations were unilateral. In one cadaver (2.27%), the middle trunk was formed by union of C7 and C8 roots and lower trunk was formed by T1 root. Upper and middle trunks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…On the contrary, study conducted in India on 44 dissected specimens has demonstrated variations in the formation of trunks in five (11.4%) cadavers. 13 Additional report has indicated variation on the superior trunk in two plexuses out of 54 brachial plexuses. 8 This study depicted that the C5 pierces scalenius anterior before joining C6 to form the UT in one cadaver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, study conducted in India on 44 dissected specimens has demonstrated variations in the formation of trunks in five (11.4%) cadavers. 13 Additional report has indicated variation on the superior trunk in two plexuses out of 54 brachial plexuses. 8 This study depicted that the C5 pierces scalenius anterior before joining C6 to form the UT in one cadaver.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the study conducted in India using 44 specimens reported that the C5 root pierced scalenius anterior before joining C6 to form the UT in three (6.81%) specimens. 13 The limitation of the study includes the inability of obtaining large number of specimens or cadavers. Besides, most of the cadavers which have been used in this study were dissected bodies for teaching purpose, so some of the structures needed were destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Shetty et al 13 found unilateral variations in the formation of the trunks in five (11.3%) of 44 cadavers investigated. In one cadaver (2.27%), the middle trunk was formed by the union of C7 and C8 roots, and the lower trunk was formed by the T1 root.…”
Section: Discussionmentioning
confidence: 89%
“…Shetty, Satheesha and Madahv (2011) reported the middle trunk being formed by the union of C7 and C8 and the inferior trunk being formed by the nervous root of T1 in 2,27% of the cases. The fusion of the superior trunk and the middle trunk in the posterior triangle of the neck also was described by Shetty, Satheesha and Madahv (2011). Matejcik (2003) reported a case of bilateral fusion of the superior trunk and the middle trunk.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we'll concentrate on the variations involving the ventral roots of the cervical nerves and its relationship with the scalene muscles. Despite of the fact that the anatomic variations of the brachial plexus in general not change the normal function of the superior limb, its knowledge and identification is of an extreme importance in the achievement in the realization of orthopedic and neurosurgery interventions in the cervical region (SHETTY, SATHEESHA and MADAHV, 2011).…”
Section: Introductionmentioning
confidence: 99%